Transcriptome sequencing leads to an improved understanding of the infection mechanism of Alternaria solani in potato - Jia Jiang; Xuhao Guo; Huanhuan Tan; Mingya Ding; Fangming Liu; Zhihui Yang; Jiehua Zhu (BMC Plant Biology, 2023)
Abstract Background Alternaria solani (A. solani), the main pathogen of potato early blight, causes serious yield reductions every year. The application of fungicides is the most common and effective method of controlling Alternaria-caused diseases. The differentially expressed transcripts of A. solani infecting potato were identified, revealing a group of valuable candidate genes for a systematic analysis to increase the understanding of the molecular pathogenesis of A. solani, and providing scientific data for formulating additional measures to prevent and control potato early blight. In this study, a deep RNA-sequencing approach was applied to gain insights into A. solani pathogenesis. At 3, 4, and 5 days post inoculation (dpi), RNA samples from the susceptible potato cultivar Favorita infected with A. solani strain HWC-168, were sequenced and utilized for transcriptome analysis, and compared to the transcriptome obtained 0 dpi. Results A total of 4430 (2167 upregulated, 2263 downregulated), 4736 (2312 upregulated, 2424 downregulated), and 5043 (2411 upregulated, 2632 downregulated) genes were differentially expressed 3, 4 and 5 dpi, respectively, compared with genes analysed at 0 dpi. KEGG enrichment analysis showed that genes involved in the pathways of amino acid metabolism, glucose metabolism, and enzyme activity were significantly differentially expressed at the late infection stage. Correspondingly, symptoms developed rapidly during the late stage of A. solani infection. In addition, a short time-series expression miner (STEM) assay was performed to analyse the gene expression patterns of A. solani and Profile 17 and 19 showed significant change trends 3, 4 and 5 dpi. Both profiles, but especially Profile 17, included enzymes, including transferases, oxidoreductases, hydrolases and carbohydrate-active enzymes (CAZYmes), which may play important roles in late fungal infection. Furthermore, possible candidate effectors were identified through the adopted pipelines, with 137 differentially expressed small secreted proteins identified, including some enzymes and proteins with unknown functions. Conclusions Collectively, the data presented in this study show that amino acid metabolism, and glucose metabolism pathways, and specific pathway-related enzymes may be key putative pathogenic factors, and play important roles in late stage A. solani infection. These results contribute to a broader base of knowledge of A. solani pathogenesis in potato, as indicated by the transcriptional level analysis, and provide clues for determining the effectors of A. solani infection.